1986
DOI: 10.1136/hrt.56.5.440
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative immunological response against contractile proteins after coronary bypass surgery.

Abstract: The pathogenesis of post-cardiac injury syndronme was studied prospectively in 62 patients who underwent coronary bypass grafting. Preoperative and serial postoperative titres of actin and myosin antibodies were measured by an enzyme linked immunosorbent assay. Perioperative cumulative release of serum aspartate and alanine aminotransferases, lactate dehydrogenase, and creatine kinase was calculated by approximation formulas that are used to estimate infarct size. Complete post-cardiac injury syndrome develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…They found a significant correlation between the frequency and intensity of the syndrome and the ratio of post-operative to pre-operative titers of antiactin and anti-myosin antibodies. 13 Contrary to these reports suggesting a pathogenetic importance of AHA, Hoffman et al reported that the development of AHA was epiphenomenon rather than cause of PCIS. They examined the time course of the appearance and disappearance of AHA in the circulation in 20 patients undergoing elective coronary artery bypass grafting.…”
Section: Discussionmentioning
confidence: 64%
“…They found a significant correlation between the frequency and intensity of the syndrome and the ratio of post-operative to pre-operative titers of antiactin and anti-myosin antibodies. 13 Contrary to these reports suggesting a pathogenetic importance of AHA, Hoffman et al reported that the development of AHA was epiphenomenon rather than cause of PCIS. They examined the time course of the appearance and disappearance of AHA in the circulation in 20 patients undergoing elective coronary artery bypass grafting.…”
Section: Discussionmentioning
confidence: 64%
“…[28] The development of Dressler's syndrome is considered to be immune-mediated with involvement of pericardium, pleura and lungs. [29][30][31] In the case of our patient, Takotsubo cardiomyopathy developed into Dressler's syndrome 2 weeks later. To note, a complete immune panel was unfortunately not established.…”
Section: Discussionmentioning
confidence: 99%
“…A low correlation may be particularly associated with viral myocarditis and idiopathic cardiomyopathy, where there is a protracted interval between the initial damage to the myocardium and the development of disease. Another factor may be that these antibodies are produced only in a subset of patients, since not all individuals undergoing cardiac surgery or who incur myocardial infarcts develop PCIS [16][17][18][19]. It is likely that those individuals who develop myosin autoantibodies are genetically predisposed to inflammatory heart disease.…”
Section: Myosin Antibodies and Their Association With Diseasementioning
confidence: 99%
“…Only a few investigators have attempted to demonstrate a myosin-specific response [16][17][18][19]. Myosin antibodies have been detected using an enzyme-linked immunosorbant assay (ELISA) with rabbit cardiac heavy meromyosin as the target.…”
Section: Myosin Antibodies and Their Association With Diseasementioning
confidence: 99%